New insights into geology and geochemistry of the Kerch seep area in the Black Sea. - Pape, Thomas; Haeckel, Matthias; Bohrmann, Gerhard (PANGAEA, 2020)
Concentrations of methane (headspace gas) in gravity cores and mini cores from the Kerch Seep area, Black Sea.
Concentrations of methane (headspace gas) in gravity cores and mini cores from the Kerch Seep area, Black Sea
Keywords: Black Sea; Center for Marine Environmental Sciences; ex situ; gravity core; Kerch seep area; M84/2; MARUM; methane concentrations; mini core